Synthesis, structure and characterization of hydrothermally synthesized Ag-TiO2 nano-structures onto Ni filters using electrophoretic deposition - Noberi, Cansu; Kaya, Figen; Kaya, Cengiz (ELSEVIER SCI LTD, 2016)
Nanosize Ag-TiO2 composite particles with various Ag contents were synthesized by hydrothermal synthesis (HS) at 180 degrees C for 2 h. The effects of Ag content on the particle size, structure and morphology of the synthesized particles were investigated. Stable ethanol based colloidal suspensions containing Ag-TiO2 particles were prepared and coated onto 3-D metallic filters by electrophoretic deposition (EPD) using a deposition time of 5 min and an applied voltage of 30 V D.C. It is shown that the particle size of Ag-TiO2 is increased with increased Ag content and with the addition of 15 wt% Ag to TiO(2)changes the spherical morphology into needle-like shape. It is also shown that 3-DNi filters can successfully be coated by EPD using the synthesized nano composite particles. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Nano particles; Ag-TiO2; Hydrothermal synthesis; Electrophoretic deposition; 3-D filter; SILVER NANOPARTICLES; PHASE-TRANSITION; TITANIA; AG; Materials Science